OPTIMASI STOK AYAM POTONG MENGGUNAKAN METODE FUZZY TSUKAMOTO DI RUMAH MAKAN BOYOLALI - Helfa Renita Berlian; Muhammad Hasbi; Kustanto Kustanto (STMIK Sinar Nusantara, 2020)
A developing business must have a goal so that activities in a business can be directed. So that the business can achieve these goals, it is necessary to have a careful plan to determine the production of products that are made to meet market needs. Therefore, this study aims to determine the optimization of the stock chicken stock application system at Boyolali Restaurant using the Fuzzy Tsukamoto method based on sales data and restaurant needs. Boyolali Restaurant also has a disadvantage, namely controlling stock of chicken that is still not suitable and not optimal for each day due to the number of requests that continue to vary each day The number of products produced is something that influences competition in the business world. The type of data consists of Primary Data, There are 2 kinds of primary data that the authors do, namely: Observation Method, Interview Method and Secondary Data in the form of Library Studies. Data Analysis with system analysis using the Flowchart system, input output design and system testing. The results of this study are making web applications with the PHP programming language with a MySQL database. The test carried out is the validity test by comparing the data of real chicken orders and the chicken chicken order data from the results of fuzzy calculations from the application is valid. Comparison with the difference between real data and fuzzy calculation results with the highest difference order 347 pieces of chicken stock and the lowest difference of 3 pieces of chicken stock with an average difference in stock orders is 70 stocks of chicken pieces. Comparison of real order data with fuzzy results has an accuracy above 70% with an average accuracy of 93%.